Meiofauna Community Structure in Maludam River, Sarawak - Muhammad Nur Arif, Bin Othman (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Maludam River is one of the rivers located in Sarawak and it is the habitat for many aquatic animals and plants. The main objective of the study was to determine the relationship between meiofauna community and environmental parameters. The sampling was done on 24th and 25th August 2013. Six stations were selected which runs from freshwater to estuarine regions. Eight taxa were recorded in Maludam River such as Nematoda, Polychaeta, Oligochaeta, Tardigrada, Copepoda, Insecta, Gastropoda larvae and Bivalvia larvae. Copepoda was the common meiofauna found in all stations. Station 6 had recorded the highest species density (182.46 ind./10 cm2 ) while the lowest species density was recorded in station 2 (10.61 ind./ 10 cm2 ). Chlorophyll a shows a strong positive correlation with species diversity (r= 0.917, p= 0.005) and species richness (r= 0.883, p= 0.010). The data gathered from the study could be used as baseline data for future management of Maludam River.